Experimental Investigation of Ultrasonic Pulse Velocity (UPV) Test Specimen in assessing the Strength of Steel Fiber Reinforced Concrete Structure - Zulkifli, Nuralia Izzaty; Alisibramulisi, Anizahyati; Saari, Nadiah; Hassan, Rohana; Shaffie, Ekarizan; Mohamad Bhkari, Norshariza; Muhd Sidek, Muhd Norhasri (Journal of Advanced Industrial Technology and Application, 2021)
This study aims to conduct the Ultrasonic Pulse Velocity (UPV) test and compressive strength test of Steel Fiber Reinforced Concrete (SFRC). This paper also examines the correlation of UPV test data and compressive strength test data for SFRC specimens. The experiments were carried out with the same value of the water-cement ratio, superplasticizer but different fiber volumes of steel fiber. Twelve prism sizes 100mm x 100mm x 500mm were casted and 0.5%, 1.0%, and 1.5% of steel fiber reinforced concrete were added and the prisms undergone curing for 7, 14 and 28 days. The highest value of the UPV test at the x-axis is SFRC-0.5%, 6.26 km/s at seven days and 6.8377 km/s at 14 days. The highest value of the UPV test at the y-axis is SFR-0.5%, 6.68 km/s at seven days and 6.34 km/s at 28 days. The grading is still in the excellent concrete quality based on BS1881. The highest value of compressive strength is SFRC-1.0%, 193.2 MPa at 14 days. The R-squared value for the correlation coefficient between UPV result and the compressive strength result at the x-axis and y-axis is 0.9963 and 0.9966 respectively which is near to 1.0 and can be considered as strongly correlated. The correlation equation obtained can be used to predict compressive strength based on UPV data for steel fiber addition up to 1.5% volume.  Thus, it can be concluded that percentage of steel fiber added, affect the strength of the tested concrete specimens and the optimized value of steel fiber added is at 1% in this study